2004
DOI: 10.1074/jbc.m313487200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I Activates Cellular cAMP Signaling through the ABCA1 Transporter

Abstract: It has been suggested that the signal transduction pathway initiated by apoA-I activates key proteins involved in cellular lipid efflux. We investigated apoA-Imediated cAMP signaling in cultured human fibroblasts induced with (22R)-hydroxycholesterol and 9-cis-retinoic acid (stimulated cells). Treatment of stimulated fibroblasts with apoA-I for short periods of time (<45 min) increased ATP binding cassette A1 (ABCA1) phosphorylation in a concentration-dependent manner. Concomitantly, apoA-I increased the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 42 publications
4
68
1
1
Order By: Relevance
“…In light of this, apoA-I may have important implications in the activation of ABCA1, consistent with our previous study (19) which showed that brief treatment of 22OH/9CRA-stimulated fibroblasts or Chinese hamster ovary cells overexpressing ABCA1 with apoA-I triggered cAMP production and consequently induced ABCA1phosphorylationviaacAMP-dependent protein kinase-dependent mechanism. This is in agreement with the finding of Oram and Heinecke (34) that ABCA1 activity could be regulated by different signaling processes, including the JAK2 pathway.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In light of this, apoA-I may have important implications in the activation of ABCA1, consistent with our previous study (19) which showed that brief treatment of 22OH/9CRA-stimulated fibroblasts or Chinese hamster ovary cells overexpressing ABCA1 with apoA-I triggered cAMP production and consequently induced ABCA1phosphorylationviaacAMP-dependent protein kinase-dependent mechanism. This is in agreement with the finding of Oram and Heinecke (34) that ABCA1 activity could be regulated by different signaling processes, including the JAK2 pathway.…”
Section: Discussionsupporting
confidence: 75%
“…B, normal fibroblasts stimulated with 22OH/9CRA in the presence or absence of 30-fold excess of unlabeled apoA-I, unstimulated normal fibroblasts, and ABCA1 mutant (Q597R) were incubated with 10 g/ml drastically reduced the association of 125 I-apoA-I with both the PM and ICCs. We have previously reported that the Q597R-ABCA1 mutant does not bind apoA-I but is expressed normally and localizes to the cell surface (19).…”
Section: Development Of a Quantitative Biotinylation Assay-tomentioning
confidence: 99%
“…Another inhibitor of ERK1/2, U0126 (2 M, IC 50 values were 72 and 58 nM for ERK1 and ERK2, respectively) also markedly increased macrophage free cholesterol efflux (ϳ3-fold). In contrast, inhibition of other kinases, such as protein kinase C by calphostin C (1 M, IC 50 did not influence macrophage free cholesterol efflux to apoAI. Therefore, enhancement of macrophage cholesterol efflux to apoAI appears to be ERK1/2 inhibition-selective.…”
Section: Regulation Of Macrophage Freementioning
confidence: 88%
“…However, PKA activity has no effect on ABCA1 expression (48,49). ApoAI and synthetic amphiphilic helical peptides increase ABCA1 protein stability by activating PKA (50,51). ApoAI also phosphorylates ABCA1 through protein kinase C␣ to enhance ABCA1 protein stability (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, when too much cholesterol enters cells, ABC-A1 forms a complex with the G protein α subunit (Gαs), which activates adenylate cyclase to produce more cAMP. This process results in the activation of PKA, which phosphorylates ABC-A1 to inhibit ABC-A1 degradation and to promote phospholipid and cholesterol efflux [50] . Recently, we found that the addition of NO-1886 (0.1 g/kg body weight/day) to the diet of high-fat/ high-sucrose/high-cholesterol-fed Chinese Bama minipigs for 5 months significantly reduced atherosclerotic lesions and significantly increased plasma HDL-c and apolipoprotein AI levels [39] .…”
Section: Extracellular Hdl Trafficking Systemmentioning
confidence: 99%